The correlation between the implementation of EBI and smooth breast milk production in breastfeeding mothers - Kristiana, Dita; Bonggili, Delvianita Anggraeni (International Journal of Health Science and Technology, 2024)
Some mothers experience breastfeeding problems, the most common problem experienced by mothers after giving birth is that breast milk does not flow smoothly or does not come out. The impact of unsmooth milk production for mothers is swollen breasts, mastitis, blocked milk ducts, and lack of confidence in breastfeeding babies. In addition, the impact on babies is that babies do not like to breastfeed and the increase in the provision of breast milk substitutes, so that it affects the nutritional needs of babies. The purpose of this study is to determine the corellation between the implementation of early breastfeeding initiation and the smooth discharge of breast milk at the Gamping 1 Health Center. Methods This research is an analytical descriptive research with a cross-sectional approach. The sample in this study is 30 people with a total sampling technique. This research has passed the Ethical Clearance test with number 3302/KEP-UNISA/XII/2023. The instrument of this research is a questionnaire that contains several questions and written statements to the respondents. The results of the research from 30 respondents according to the variables through the chi-square test found that there was a meaningful corellation between the implementation of early breastfeeding initiation and the smooth discharge of breast milk in breastfeeding mothers in the Gamping 1 Health Center Working Area of 0.014 (p<0.05). The data and results obtained can be used as a reference and input for health workers, especially midwives as the main helpers of maternity mothers to optimize health services in initiating early breastfeeding.